2017
DOI: 10.1055/s-0037-1608686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sustained Use of Aspirin until the Time of Surgery on Outcomes following Coronary Artery Bypass Grafting: A Randomized Clinical Trial

Abstract: Sustained ASA use until the day of surgery in patients planned for elective isolated CABG can result in excessive bleeding, increased rate of reexploration, and need for more PRBC transfusion without any proven beneficial effect on reducing unfavorable postoperative outcomes. Hence, we recommend discontinuing ASA between 3 and 5 days before non-urgent CABG while keeping it on in nonelective circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In one RCT, CABG patients (n ¼ 206) received aspirin treatment that was either continued until the day of surgery or stopped 4 days earlier. 312 Rates of bleeding and transfusion of RBCs were significantly higher in patients receiving aspirin until the day of surgery (P < 0.001), and there were no significant differences in postoperative myocardial infarction or stroke. Nevertheless, the ATACAS randomised trial, conducted in 2100 patients undergoing coronary artery surgery, concluded differently as the administration of pre-operative aspirin resulted in neither a lower risk of death or thrombotic complications nor a higher risk of bleeding, including re-operation for haemorrhage, than observed with placebo.…”
Section: Evidence Summarymentioning
confidence: 86%
See 1 more Smart Citation
“…In one RCT, CABG patients (n ¼ 206) received aspirin treatment that was either continued until the day of surgery or stopped 4 days earlier. 312 Rates of bleeding and transfusion of RBCs were significantly higher in patients receiving aspirin until the day of surgery (P < 0.001), and there were no significant differences in postoperative myocardial infarction or stroke. Nevertheless, the ATACAS randomised trial, conducted in 2100 patients undergoing coronary artery surgery, concluded differently as the administration of pre-operative aspirin resulted in neither a lower risk of death or thrombotic complications nor a higher risk of bleeding, including re-operation for haemorrhage, than observed with placebo.…”
Section: Evidence Summarymentioning
confidence: 86%
“…Aspirin treatment was associated with increased chest tube drainage ( P = 0.011), although the risk of re-operation due to bleeding was not significantly increased. In one RCT, CABG patients ( n = 206) received aspirin treatment that was either continued until the day of surgery or stopped 4 days earlier 312 . Rates of bleeding and transfusion of RBCs were significantly higher in patients receiving aspirin until the day of surgery ( P < 0.001), and there were no significant differences in postoperative myocardial infarction or stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Four hundred nineteen duplicates were removed; the remaining 2408 studies were screened by title and abstract. Eighty‐one studies were identified for full‐text review; finally, 56 RCTs 15–70 comprising 61 894 patients in total were included in this study (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the 2017 EACTS Guidelines on Preoperative Medication in Adult Cardiac Surgery, 11 aspirin usage is recommended in the preoperative and postoperative periods (class IIA and class I recommendation respectively). From the perspective of stroke prevention, there was no significant difference between administration of preoperative aspirin versus its discontinuation 40,41 . Given the benefits of aspirin continuation in reducing postoperative MI, 71 this strategy is recommended unless the patient is at high risk of bleeding or refuses blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained ingestion until the day of surgery in elective can result in excessive bleeding, increased rate of reexploration, and need for more transfusions. 38 A recent comparative study of patients undergoing surgery without the use of extracorporeal circulation with or without discontinuing aspirin preoperatively showed a similar incidence of complications associated with haemorrhage. 39 Interruption of aspirin administration is no longer suggested.…”
Section: Discussionmentioning
confidence: 98%